Advising Experiences of First Year International Doctoral Students - Marijanovic, Nina; Lee, Jungmin; Teague, Thomas; Means, Sheryl (Journal of International Students, 2021)
The purpose of this qualitative study was to understand how international doctoral students were matched with their faculty advisors and how their advising experiences and satisfaction were shaped by their academic discipline. We applied the lens of developmental advising to situate the advising experiences of our sample because of the framework’s emphasis on holistic support and student development. We conducted individual semistructured interviews with 21 international doctoral students attending a large research-intensive university in the Southeast. Most participants were assigned to an interim advisor, but the data revealed concerning differences in the type of advising experiences and support based on academic discipline. This study contributes to the body of literature by exploring advisor–advisee matching among international doctoral students and by further analyzing how disciplinary cultures shape perceptions of satisfaction with advising.